Shariah compliance assessment of construction takaful claims for loss and damage - Mohd Fauzi, Puteri Nur Farah Naadia; Abdul Rashid, Khairuddin (2015)
Incessant and ascendant increases in the interest to adopt Shariah concepts in commercial transactions has encouraged business entities including contractors to employ Shariah compliance products. Currently, contractors are inclined to employ Contractor’s All Risks (CAR) Takaful to insure their works during construction. Upon any occurrence of specified risks to the construction works, contractors may submit claims and the monies received therefrom would be utilized to recover the damaged works. However, past studies claimed that the practice in assessing claims in takaful has deficiency in terms of its legitimacy from the Shariah perspectives. The current practice in assessing claims for construction works loss and damage lack of transparency and accountability with absence of standard guideline. Consequently, a study was conducted with the key objective to identify legitimacy from the Shariah perspectives in assessing claims for construction works loss and damage. The methodology used for the study combined three (3) key data sources, which are (i) review on primary religious documents i.e. Quran and hadith and practice of the assessments of construction takaful claims in Malaysia; and (ii) semi-structured interview with eight (8) experts in the fields of takaful and insurance, construction industry, and Shariah knowledge areas. The outcome of the study suggests that (i) there are various methods used by the experts in assessing claims for construction works loss and damage, and (ii) the current practice in assessing takaful claims for construction works loss and damage do not adhere fully to the requirement of the Shariah. This paper is expected to produce a summary of the legitimacy from the Shariah perspectives in making assessment for construction works loss and damage. Further research is recommended in order to develop a Shariah compliance standard procedures for the assessment of takaful claims for construction works loss and damage.